2023
DOI: 10.1177/17455057231183573
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aerobic and resistance exercise on blood pressure in uncomplicated and at risk pregnancies: A systematic review and meta-analysis

Abstract: Background: Regular exercise performed during pregnancy has been shown to reduce the risk of developing perinatal gestational hypertensive conditions. Further evidence on the exact parameters of exercise needed to explain these beneficial responses is required, within both uncomplicated and at-risk pregnancies. Objective: The aim of this systematic review and meta-analysis was to investigate the effects of aerobic and resistance exercise on blood pressure during pregnancy. Design: Systematic review and meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 110 publications
0
0
0
Order By: Relevance
“…A recent systematic review and meta-analysis that investigated the effects of aerobic and resistance exercise on blood pressure during pregnancy while experiencing clinical conditions such as gestational diabetes mellitus and obesity during pregnancy observed that exercise has the potential to decrease the typical rise in blood pressure associated with these conditions. These discoveries carry significant importance for pregnant women who are at risk of developing gestational hypertension and pre-eclampsia [49].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis that investigated the effects of aerobic and resistance exercise on blood pressure during pregnancy while experiencing clinical conditions such as gestational diabetes mellitus and obesity during pregnancy observed that exercise has the potential to decrease the typical rise in blood pressure associated with these conditions. These discoveries carry significant importance for pregnant women who are at risk of developing gestational hypertension and pre-eclampsia [49].…”
Section: Discussionmentioning
confidence: 99%
“…Because it is clear that in non-gravid populations, resistance training supports improvements in arterial blood pressure, 69 stronger evidence to show a similar effect during pregnancy is 1144 needed. 70 In addition, not all strength training is created equal. For example, CrossFit TM contains more cardiovascular involvement (complete a number of exercises as fast as possible) than traditional weightlifting (full recovery between sets), and different types of strength training should be studied individually in order to determine which yields the most benefit for pregnant women.…”
Section: A Call For Actionmentioning
confidence: 99%